Identification of a TGF-β/SMAD/lnc-UTGF positive feedback loop and its role in hepatoma metastasis - Meng-Zhi Wu (Nature Publishing Group, 2021)
Abstract Aberrant activation of the TGF-β/SMAD signaling pathway is often observed in hepatocellular carcinoma (HCC). Whether lncRNA regulates the TGF-β/SMAD signaling remains largely unknown. Here, we identified an oncogenic lncRNA that was upregulated in HCC and was transcriptionally induced by TGF-β (named lnc-UTGF, lncRNA upregulated by TGF-β). Upon TGF-β stimulation, SMAD2/3 bound to the lnc-UTGF promoter and activated lnc-UTGF expression. In turn, the TGF-β/SMAD signaling was augmented by overexpressing lnc-UTGF, but was inhibited by silencing lnc-UTGF. Mechanism investigations revealed that lnc-UTGF interacted with the mRNAs of SMAD2 and SMAD4 via complementary base-pairing, resulting in enhanced stability of SMAD2/4 mRNAs. These data suggest a novel TGF-β/SMAD/lnc-UTGF positive feedback circuitry. Subsequent gain- and loss-of-function analyses disclosed that lnc-UTGF promoted the migration and invasion of hepatoma cells, and this effect of lnc-UTGF was attenuated by repressing SMAD2/4 expression or by mutating the SMAD2/4-binding sites in lnc-UTGF. Studies using mouse models further confirmed that in vivo metastasis of hepatoma xenografts was inhibited by silencing lnc-UTGF, but was enhanced by ectopic expression of lnc-UTGF. The lnc-UTGF level was positively correlated with the SMAD2/4 levels in xenografts. Consistently, we detected an association of lnc-UTGF upregulation with increase of SMAD2, SMAD4, and their metastasis effector SNAIL1 in human HCC. And high lnc-UTGF level was also significantly associated with enhanced metastasis potential, advanced TNM stages, and worse recurrence-free survival. Conclusion: there exists a lnc-UTGF-mediated positive feedback loop of the TGF-β signaling and its deregulation promotes hepatoma metastasis. These findings may provide a new therapeutic target for HCC metastasis.